Pengaruh Quick Ratio, Working Capital Turnover, dan ROA terhadap Harga Saham Sektor Properti BEI 2019-2023 - Wira, Yudist Wira; Steffy Septiani; Kardinal (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This research aims to examine the influence of quick ratio, return on asset and working capital turn over on stock price in property and real esatate companies listed on the Indonesia Stock Excahage from 2019-2023. This research employs a quantitative method, using purposive sampling for sample selecetion. Based on criteria, a total of 94 companies were selected over a 5-year period. Data analysis includes normality test, multicollinearty test, hecteroscedasticity test, autocoreelation test, multiple linear reggeresion analysis, coefficient of determination test, F-test (simultaneous), and t-test (partial). The result indicate that, simultaneously, quick ratio, return on asset, and working capital turn over have a significant effect on stock prices. Partially, return on asset has a significant effect on stock prices, where quick ratio and working capital turn over do not have a significant effect on stock prives